The role of tauroursodeoxycholic acid on adipogenesis of human adipose-derived stem cells by modulation of ER stress - Cha, Byung-Hyun; Kim, Jin-Su; Ahn, Jong Chan; Kim, Hee-Chun; Kim, Byung-Soo; Han, Dong Keun; Park, Sang Gyu; Lee, Soo-Hong (ELSEVIER SCI LTD, 2014)
Obesity has become a serious public health problem in the developed world. Increased mass of adipose tissue in the obese is due to an increase in both the size (hypertrophy) and number (hyperplasia) of adipocytes. The chemical chaperone tauroursodeoxycholic acid (TUDCA) not only decreases endoplasmic reticulum (ER) stress, but also plays a role as a leptin-sensitizing agent for preadipocytes in mice and humans. In this study, we examine whether TUDCA has an effect on adipogenesis from human adipose-derived stem cells (hASCs). Therefore, the effect of TUDCA on ER stress, lipid accumulation, and adipogenic differentiation from hASCs was investigated using histological staining, reverse-transcriptase polymerase chain reaction (RT-PCR), and western blotting in vitro. It was found that TUDCA treatment of hASCs significantly decreases the representative ER stress marker (glucose-regulated protein 78 kDa (GRP78)), adipogenic markers (peroxisome proliferator-activated receptor gamma (PPAR gamma) and glycerol-3-phosphate dehydrogenase 1 (GPDH)), and lipid accumulation. Furthermore, we confirmed that TUDCA treatment of hASCs significantly decreased in vivo adipogenic tissue formation and ER stress comparing with PBS treatment of hASCs. The results indicate that TUDCA plays a critical role in adipogenesis from hASCs by modulating ER stress and, therefore, has potential pharmacologic and therapeutic applications as an anti-obesity agent. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: ENDOPLASMIC-RETICULUM STRESS; WEIGHT-LOSS; 3T3-L1 ADIPOCYTES; STROMAL CELLS; OBESITY; TISSUE; EXPRESSION; GLUCOSE; APOPTOSIS; DIFFERENTIATION